Prosociality from early adolescence to young adulthood: A longitudinal study of individuals with a history of language impairment. (March 2017) - Toseeb, Umar; Pickles, Andrew; Durkin, Kevin; Botting, Nicola; Conti-Ramsden, Gina
Highlights: This is the first longitudinal study of prosociality in young adults with LI. Participants with LI perceived themselves as prosocial. Ratings remained within the expected range across young adulthood (11–24 years). Two different developmental trajectories were identified for the LI group. Small to medium effects were found indicating protective effects of prosociality into adulthood. Abstract: Background: Longitudinal research into the development of prosociality contributes vitally to understanding of individual differences in psychosocial outcomes. Most of the research to date has been concerned with prosocial behaviour in typically developing young people; much less has been directed to the course of development in individuals with developmental disorders. Aims: This study reports a longitudinal investigation of prosocial behaviour in young people with language impairment (LI), and compares trajectories of development to typically developing age-matched peers (AMPs). Methods and procedures: Participants were followed from age 11 years to young adulthood (age 24 years). Outcomes and results: Participants with LI perceived themselves as prosocial; their ratings – though lower than those for the AMPs – were well within the normal range and they remained consistently so from 11 to 24 years. Two different developmental trajectories were identified for the LI group, which were stable and differed only in level of prosociality. Approximately one third of participants with LI followed a moderate prosociality trajectory whilst the majority (71%) followed a prosocial trajectory. We found evidence of protective effects of prosociality for social outcomes in young adulthood. Conclusions and implications: The findings indicate that prosociality is an area of relative strength in LI. What this paper adds?: To our knowledge, this is the first study to examine developmental changes in levels of prosociality from early adolescence to young adulthood in a cohort of young people with LI. Approximately one third of participants with LI followed a moderate prosociality trajectory whilst the majority (71%) followed a prosocial trajectory. We argue that prosociality is different to other areas of functioning in LI. Prosociality appears to be an area of relative strength and can act as a protective factor in social functioning. Prosociality was associated with better community integration in young adulthood and was significantly protective against friendship difficulties for individuals with LI. This paper also raises the thought-provoking issue of potential distal effects of early identification and intensive support for LI. It is important to note that all of the participants with LI in this study had been identified as having language difficulties in childhood and had received intensive intervention for their difficulties in language units attached to mainstream schools across England. The early identification of language difficulties and the context of early, intensive language support received in educational contexts such as language units may have nurtured socialisation processes and the development of emphatic concern, which in turn influence the development of prosociality later in young adulthood. More individual differences in prosociality have been reported for other samples drawn from a variety of schools with different educational provision and levels of language support and younger age groups, such as primary school-aged children with LI.